Mendudukkan status hukum asuransi syariah dalam tinjauan fuqaha kontemporer - Hosen, Muhammad Nadratuzzaman; Muayyad, Deden Misbahuddin (Sekolah Tinggi Agama Islam Negeri Salatiga, 2013)
Insurance Law in The contemporary Islamic Jurists Reviews. The aim of this article is to explain theinsurance points of view of contemporary Islamic jurists. In the classical fiqh literatures, discussion ofinsurance can not be found except in the book of Rad al Muhtar âala Dar al Mukhtar, this book ispublished by Ibn Abidin Hanafiyah as a Islamic Jurist. The Insurance is allowed by the majority ofcontemporary jurists, namely, insurance taâawuni based on tabarru (donation), while insurance tijari isnot allowed because it contains elements that are prohibited such as riba and gharar.